Characterization of uniaxial fatigue behavior of precipitate strengthened Cu-Ni-Si alloy (SICLANIC(TM)) - B. Saadouki; M. Elghorba; PH. Pelca; T. Sapanathan; M. Rachik (Fracture and Structural Integrity)
Fatigue tests were conducted on cylindrical bars specimens to understand the fatigue behavior of SICLANIC®. Although it displays good resistance in monotonic tension, this material weakens and shows a softening in repeated solicitation. This has been verified through a SEM observation, the Cu-Ni-Si alloy presents transgranular failure by cleavage. The MansonCoffin diagram exhibited the plastic deformation accommodation. The plastic deformation becomes periodic and decreases progressively as the cycle number increases. The approximations of Manson Coffin give fatigue parameters values which are in good agreement with the experience.